Community structure of mangroves in Brgy. Cagay, Roxas City, Capiz. - Mondragon, Dayan Kristel De Juan
The continued loss of mangroves in Capiz and elsewhere in the Philipines warrants urgetn attention. Appropriate management schemes can only be drawn after a scientific assessment of the remaining mangroves in a given area. this study aims to assess the community structure of mangroves in Brgy. Cagay, Roxas City, Capiz using accepted ecological indicators as well as to correlate this with physical and chemial parameters such as soil and water temperature. Community structure is described in terms of the following pararmeters: Stand basal area, stems per hectare, relative density, relative dominance, relative frequently, importance values and Shannon Index of Dviersity. This study will provide information on the recent status of mangrove in Brgy. Cagay Roxas City, Capiz. Twelve mangrove species representing seven families were identified in Brgy. Cagay, Roxas City, Capiz. These are: Acanthus ebracteatus, Avicennia alba, Avicennia marina, Avicennia officinalis, Avicennia rumphiana, Ceriops decandra, Exoecaria agallocha, Nypa fruiticans, Rhizophora mucronata, Rhizophora stylosa, Sonneratia alba, and Xylocarpus moluccensis. Some species were found outside the plots but were not included in the quantitative analysis. These species are Acanthus ebracteatus, Avicennia officinalis, Ceriops decandra, Exocharia agallocha, Nypa fruiticans and Xylocarpus moluccensis. Avicennia marina has the highest basal area, stems per hectare, relative density, relative dominance and the most important species with the values of : 46.32 m squared /ha; 22,300 trees per hectare, and 460 trees per hectare, and 35.67 percent respectively. The importance value for Aviccenia marina is 521.29. Avicennia alba, on the other hand, has the highest relative frequency with the value of 33.33 Avicennia marina has the highest seedling density, whereas Rhizophora mucronata has the highest sapling density. The species with the lowest seedling density is Sonneratia alba and Avicennia marina has the lowest sapling density percent Brgy. Cagay, Roxas City has a low diversity of 0.430 and with only twelve true mangrove species identified. The dominance of Avicennia marina is attributed to its preference for high salinity and sandy, muddy soil as substrate. In addition, the relatively protected nature of the area also contributed to the development of the observed community structure.